NlATG1 Gene Participates in Regulating Autophagy and Fission of Mitochondria in the Brown Planthopper, Nilaparvata lugens - Yu, Feifei; Hao, Peiying; Ye, Chenglong; Feng, Yalin; Pang, Kun; Yu, Xiaoping (Frontiers in Physiology, 2020)
Autophagy plays multiple roles in regulating various physiological processes in cells. However, we currently lack a systematic analysis of autophagy and the autophagy-related gene 1 ATG1 in the brown planthopper (BPH, Nilaparvata lugens), one of the most destructive insect pests of rice. In this study, the full-length cDNA of an autophagy-related gene, NlATG1, was cloned from BPH. Real-time qPCR (RT-qPCR) revealed that this NlATG1 gene was expressed differently across developmental stages, at higher levels in nymphs but lower levels in adults. RNA interference with dsNlATG1 significantly decreased the mRNA level of the target gene to 14.6% at day 4, compared with that of the dsGFP control group. The survival of dsNlATG1-treated group decreased significantly from day 4 onward, dropping to 48.3% on day 8. Examination using transmission electron microscopy (TEM) showed that epithelial cells of the BPH’s midgut in the dsNlATG1-treated group had less autophagic vacuoles than did the dsGFP control, and knockdown of NlATG1 clearly inhibited the starvation-induced autophagy response in this insect. RNA interference of NlATG1 upregulated the NlFis1 gene involved in mitochondrial fission, leading to reductions in mitochondrial width and area. Furthermore, knockdown of NlATG1 also decreased the ATP content and accumulation of glycogen. Together, these results demonstrate that the NlATG1 gene participates in regulating autophagy and fission of mitochondria in the brown planthopper, making it a potentially promising target for pest control given its key role in autophagy, including maintaining the normal structure and function of mitochondria.